Development of sweet and spicy alamang (Acetes Spp) crunchies - Advincula, Maria Athena; Quintos, Sarah V. (1992., 1992)
A study of the rejects of an alamang exporting company was conducted to formulate a new product, Sweet & Spicy Alamang Crunchies. The rejects consisted of dried alamang which did not meet the quality standards of the company. Sweet & spicy alamang crunchies was basically patterned after sweet and spicy squid and peanut brittle. The study consisted of two phases. Phase 1 dealt with the determination of the best product formulation by allowing eleven panelists to subjectively evaluate three formulations. Through the analysis of variance, the best formulation was found to be sample 663 or formulation 1. This was characterized to have a dark golden brown color, distinct alamang odor and flavor, just right sweet-spicy flavor, and a crunchy to tough texture. The panelists gave sample 663 the highest rank of 7.9 or "likely moderately" to "like very much" in the Hedonic rating scale. The best product from Phase I was further analyzed in Phase II at the three points namely: the raw material, the in-process operation and the finished product. The raw material, alamang, was objectively measured to have a light golden brown color or 10YR 8/4 in the Munsell color system, a slightly alkaline pH of 7.35, bulk density of 0.45 g/ml and moisture content of 11.8%. In the in-process operation, factors such as the temperature and time of melting the sugar, the recovery weight and color of the product were determined. The various critical control points of production were likewise established. The finished product was found to have a dark golden brown color or 10YR 4/4 in the Munsell color system, a pH of 7.25, bulk density of 0.64 g/ml, moisture content of 2205% and fat, protein and ash content of 16.5%, 27.0%, and 0.25% respectively. Tests for yeast and mold count of two samples showed negative growth while an average growth of 3.3 x10^4 colony forming units (cfu) for the two samples was recorded for the total plate count. The product was subjectively evaluated to determine any significant correlation between each quality attribute and the general acceptability of the product. Only the texture was found to have no significant correlation to general acceptability. This indicated that the panelists showed preference to the product in terms of all the quality attributes except texture.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Shrimp paste